Cryoimmobilized anther analysis reveals new ultrastructural insights into Rhynchospora (Cyperaceae) asymmetrical microsporogenesis - Rocha, Danilo M.; Neumann, Ulla; Nogueira, Fernanda M.; Tsipas, Georgios; Vanzela, André L. L.; Marques, André (Frontiers in Plant Science, 2025)
IntroductionThe Cyperaceae family is distinguished by holocentric chromosomes and a distinctive microsporogenesis process, which includes inverted meiosis, asymmetric tetrad formation, selective cell death, and the formation of pseudomonad pollen. Despite significant advances, the ultrastructural details of these processes remain poorly understood.MethodsThis study provides a detailed analysis of microsporogenesis in Rhynchospora pubera using high-pressure freezing, freeze substitution, and transmission electron microscopy, significantly enhancing ultrastructural resolution.Results and discussionOur findings reveal that intracellular organization differs from model species Arabidopsis thaliana and drives nuclear selection, with endoplasmic reticulum vesicles organizing meiotic spindles. Microtubules attach to centromeres located deep within holocentric chromosomes, while extensive cytoplasmic connections facilitate material exchange until callose deposition encloses meiocytes. Lipid distribution contributes to cell asymmetry, resulting in the characteristic asymmetric tetrads. Following meiosis, cytoskeletal elements coordinate nuclear migration and cell plate formation. Pseudomonads exhibit reconfigurations in the endomembrane system, particularly involving the endoplasmic reticulum, which supports functional cell differentiation. Complementary histochemical analyses corroborate these findings, providing insights into the cellular processes governing Rhynchospora microsporogenesis. These findings contribute to a deeper understanding of the developmental processes of Cyperaceae pollen, thereby facilitating future investigations of the underlying molecular mechanisms.